2019
DOI: 10.3390/nu11122989
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Understanding of Curcumin’s Therapeutic Effects in Lung Cancer

Abstract: Lung cancer is among the most common cancers with a high mortality rate worldwide. Despite the significant advances in diagnostic and therapeutic approaches, lung cancer prognoses and survival rates remain poor due to late diagnosis, drug resistance, and adverse effects. Therefore, new intervention therapies, such as the use of natural compounds with decreased toxicities, have been considered in lung cancer therapy. Curcumin, a natural occurring polyphenol derived from turmeric (Curcuma longa) has been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 269 publications
(270 reference statements)
1
62
0
1
Order By: Relevance
“…Curcumin has been demonstrated to mediate anti-proliferative effect via STAT-3, EGFR, forkhead box O3 (FOXO3a), eukaryotic initiation factors (eIFs), and transforming growth factor-beta (TGF-β) (Tajuddin, Lajis, Abas, Othman, & Naidu, 2019), whereas whether these molecular targets play an important role in curcumin-mediated phenotype and function change of CAFs needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has been demonstrated to mediate anti-proliferative effect via STAT-3, EGFR, forkhead box O3 (FOXO3a), eukaryotic initiation factors (eIFs), and transforming growth factor-beta (TGF-β) (Tajuddin, Lajis, Abas, Othman, & Naidu, 2019), whereas whether these molecular targets play an important role in curcumin-mediated phenotype and function change of CAFs needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin (diferuloylmethane) is one of the most studied phytochemicals found in plants Curcuma longa (Linn) and has been shown to possess strong antioxidant, anti-inflammatory, and anticancer potential over a range of human cancers [15,16]. In various cancers, curcumin has been shown to inhibit growth and proliferation of cancer cells by targeting various survival pathways, including JAK/STAT3, PI3-kinase/AKT, Transforming growth factor beta (TGF-β), Epidermal Growth Factor Receptor (EFGR), and NF-кB [17][18][19][20][21]. In addition, there is attenuation of the transcriptional expression of regulatory proteins associated with programmed cell death or apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is attenuation of the transcriptional expression of regulatory proteins associated with programmed cell death or apoptosis. Further, it is also involved in the modulation of aberrant epigenetics mechanisms and the expression of noncoding RNA [20]. Interestingly, a number of studies have shown that curcumin exerts its pharmacological action by targeting JAK/STAT3 signaling [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…There is a general consensus that considering treatment strategies using natural product(s) is important for improving the quality of life and prognosis of cancer patients. In fact, there is a report that curcumin, a natural occurring polyphenol derived from turmeric (Curcuma longa), had anti-cancer effects via suppression of cancer cell proliferation, invasion, and metastasis in lung cancer cells [9]. The authors also showed that regulation of microRNA expression plays important roles in the curcumin-induced anti-cancer effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is a report that curcumin, a natural occurring polyphenol derived from turmeric (Curcuma longa), had anti-cancer effects via suppression of cancer cell proliferation, invasion, and metastasis in lung cancer cells [9]. The authors also showed that regulation of microRNA expression plays important roles in the curcumin-induced anti-cancer effects [9]. Furthermore, Yiqi Huayu Jiedu decoction, which comprises various Chinese herbs and natural compounds, was reported to increase the anti-cancer effects of standard chemotherapy in patients with stage III gastric cancer after radical gastrectomy and improve the quality of life of patients [10].…”
Section: Introductionmentioning
confidence: 99%